Sentiment analysis in Bengali Text using NLP - Sarkar, Ankon; Sourav, Aishwarja Paul; Ahmed, Rezvi (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.